Rancang Bangun Game Edukasi Bencana Alam Menggunakan Metode MDLC - Nisya, Intan Sofiatun; Wulansari, Ossy Dwi Endah; Wartariyus, Wartariyus (Penerbit Goodwood, 2023)
Purpose: Educational games about natural disasters in Indonesia, as a provision of learning tools to foster children's interest in learning knowledge and emergency response efforts to natural disasters, through digital games that make children happy and easy to understand material. Research Methodology: In making this Natural Disaster Educational Game, the Multimedia Development Life Cycle (MDLC) system development method is implemented which consists of six stages, namely concept, design, material collecting, assembly, testing. and distribution (distribution). This research involved elementary school students and teachers as well as employees of the national disaster management agency in the city of Bandar Lampung. Result: A multimedia-based